Molecular epidemiology and characterization of porcine adenoviruses in pigs with diarrhea in Thailand - Kattareeya Kumthip (2018)
© 2018 Pigs have been assumed as a source of human viral infections. Surveillance of viruses in animals is essential to evaluate the risk to human and animal health and to determine economic impact. A number of studies focused mainly on well- known enteritis viruses such as porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), and porcine group A rotavirus (PRVA), however, little data is available for porcine adenovirus (PAdV). In this study, the presence of PAdV was investigated in fecal samples collected from piglets with and without diarrhea from 31 commercial pig farms in northern Thailand. A total of 781 fecal specimens (516 from diarrheic piglets and 265 from non-diarrheic piglets) were screened for adenovirus using nested-PCR. Initial screening both in diarrheic and non-diarrheic piglets showed the overall prevalence of PAdV infection in piglets at 16.9% (132/781). Co-infection with PRVA was found in 24 out of 132 (18.2%) PAdV positive cases whereas PAdV mono-infection was observed at 81.8% (108/132). The prevalence of PAdV infection in diarrheic piglets (24.2%, 102/516) was significantly higher than those detected in non-diarrheic piglets (2.6%, 7/265). Most of PAdV detected in this study (97%, 128/132) were genotype 3 while the other 4 PAdV positive samples were non identifiable genotype. Phylogenetic analysis revealed that the viruses detected in diarrheic and non-diarrheic piglets displayed a closely related (95.4 to 100%) nucleotide sequence identity. To our knowledge, this is the first report on the epidemiology and molecular characterization of PAdV in piglets in Thailand.